Relationship between habitat, densities and metabolic profile in brown hares (Lepus europaeus Pallas) - Marco Bagliacca; Marco Ferretti; Antonio Lavazza; Gisella Paci (Italian Journal of Animal Science, 2010)
Some habitat traits and haematic parameters were studied to understand the relationships between the hare densities, habitat characteristics and physiological and nutritional condition of the animals. A total of 33 protected areas, reserved for wild game reproduction, located in the Province of Florence (Central Italy), were monitored during a 2-year period. In each protected area the hares were submitted to census. The habitat features of the protected areas were studied and the following parameters were categorised: altitude; cleared-land/total-land ratio; main exposure; main ground composition; water availability; main slope; anthropogenic presence; predator presence; wooded borders; presence of trees and shrubs; surveillance against hunting; demographic predator control; kind of cultivation; unharvested crops for game. After the census the hares were captured for translocation outside in “free” hunting areas. During capture the hares were put in darkened, wooden capture-boxes and remained inside for a variable period of time (10min to 3h). A sample of 3 to 7 hares, captured per year and per each protected area, were removed from the boxes (physically restrained, with covered eyes) for blood sample collection, sex, age and live weight determination. The following analyses were performed on frozen plasma samples: ALanine aminoTransferase (ALT), ASpartate aminoTransferase (AST), glucose, cholesterol, Blood Urea Nitrogen (BUN), Ca, P, Mg, Na, K, and Cl concentrations. The relationship between hare density and habitat characteristics was analysed by single regressions analysis. Then the habitat characteristics were subjected to multivariate analysis in relationship to hare body condition. The haematic parameters were analysed by least square means considering habitat traits, animal density, age and sex, as main categorical factors, interaction sex*age, and “pregnant and non-reproducing” nested within sex. Results showed that the highest density and best body conditions can be found in highlands, open fields with low tree presence and wooded borders, medium mixture soils, scarce predator presence and limited anthropogenic presence and with abundant water availability and shrubbiness. The study of the absolute values of metabolic profile, indicator of the physiological and nutritional condition of the reared animals, did not show any nutritional winter deficiency in wild hares and, as census data, should be repeated for several years since, probably, only their variations can be used as indicators of preliminary problems.